Cancelamento de cirurgias eletivas: dos motivos à compreensão do itinerário Agendamento-Centro Cirúrgico - Santos, Gisele Aparecida Alves Corral dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objectives. (a) To characterize the cancellations of elective surgeries for clinical and non-clinical reasons, in 2013, as well as check for influence of seasonality in the period from 2010 to 2013; (b) to understand the experience of the involved actors in canceled elective surgical itinerary Surgical Scheduling - Ambulatory - Inpatient Units - Sterilized Material Center (CME) - Surgical Center (CC); (c) to elaborate theoretical model representing this experience. Methods. Mixed research, being the first a quantitative design, comprising secondary data from a Public Hospital of São Paulo database, about the surgical cancellations occurred in 2013, to achieve the objective (a). Descriptive statistics was applied, while the Poisson regression model adjusted to identify monthly differences was applied only to analyze seasonal trends concerning reasons for cancelations. The second method applied was qualitative, to meet the objectives (b) and (c). Semi-structured and individual interviews were conducted with the actors of the units which comprised the surgical itinerary, totaling 21 professionals: three doctors, 11 nurses, five technician nurses and two administrative officers. The interviews were recorded, transcribed and analyzed according to the steps of the Grounded Theory. Results. From 8.443 (100%) scheduled as elective surgeries, 7 870 (93.21%) were performed, and 573 (6.79%) canceled. Considering these 573 (100%), 48.33% were for medical reasons and 46.40% for non-clinical. Among the non-clinical reasons of surgical cancellation, predominated the ones referring to medical reasons, categorized as requested by the surgeon / change in conduct (17.93%), followed by patient not hospitalized (8.96%). Cancellations reached peaks at 7:00 AM and at 01:30 PM, due to lack of the patient's clinical conditions, and request of the Surgeon / change in conduct. Children and the elderly totaled 61.86% of ...

Objetivos. (a) caracterizar os cancelamentos de cirurgias eletivas quanto aos motivos clínicos e não clínicos, no ano de 2013, assim como verificar se existe influência da sazonalidade, no período de 2010 a 2013; (b) compreender a experiência dos atores envolvidos no itinerário cirúrgico eletivo cancelado - Agendamento cirúrgico - Ambulatório - Acolhimento - Unidades de internação - Central de Material Esterilizado (CME) - Centro Cirúrgico (CC); (c) elaborar modelo teórico representativo dessa experiência. Métodos. Pesquisa mista, sendo a primeira quantitativa, com dados secundários, extraídos de banco de dados de um Hospital Público do Estado de São Paulo, acerca dos cancelamentos cirúrgicos ocorridos em 2013, para alcançar o objetivo (a). Utilizou-se a estatística descritiva e especificamente para analisar as tendências sazonais relativas aos motivos de cancelamentos o modelo de regressão de Poisson, ajustado para identificar as diferenças mensais. O segundo método empregado foi o qualitativo, visando atender os objetivos (b) e (c). Realizou-se entrevista semiestruturada e individual com atores atuantes nos segmentos que compuseram o itinerário cirúrgico, totalizando 21: três médicos, 11 enfermeiros, cinco técnicos de enfermagem e dois oficiais administrativos. As entrevistas foram gravadas, transcritas na íntegra e analisadas segundo os passos da Teoria Fundamentada nos Dados. Resultados. Das 8.443 (100%) cirurgias eletivas agendadas, realizaram-se 7.870 (93,21%) e suspenderam-se 573 (6,79%). Considerando essas 573 (100%), 48,33% foram por razões clínicas e 46,40% não clínicas. Dentre os motivos não clínicos de cancelamento cirúrgico, preponderaram os relacionados às razões médicas, categorizadas como: a pedido do cirurgião/mudança de conduta (17,93%), seguida por paciente não internou (8,96%). Os picos de cancelamentos deram-se às 07h00 e às 13h30, por falta de condições clínicas...
Cancellation of elective surgery: from reason to understanding of the Scheduling Sector-Surgical Center itinerary
Keywords: Cuidados médicos - Avaliação; Centros cirúrgicos; Tratamento cirurgico; Cancelamento de cirurgia; Assistência hospitalar; Indicadores de qualidade em assistência à saúde; Hospital care